1980
DOI: 10.1128/jb.144.3.1152-1158.1980
|View full text |Cite
|
Sign up to set email alerts
|

Myceloid growth of Arthrobacter globiformis and other Arthrobacter species

Abstract: Transitory myceloid growth occurs in certain complex media with Arthrobacter globiformis strain ATCC 8010. This type of growth, however, was not observed in a medium which contained an array of metal ions but did not contain agents able to complex metal ions. Addition of metal-complexing agents to this medium caused an interruption in the life cycle of strain 8010 so that growth occurred only as the myceloid form. It appeared that manganese was the critical metal that was removed by the metal-complexing agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Whereas the doubling time for the wild-type was 2.5 h, for the mutant it was 3.3 h, approximating the 3.2 h doubling time of the wild-type grown in salt-amended Luria broth (LB). When early log-phase cells were examined by phase-contrast microscopy, we observed extensive aggregate formation by the mutant, similar to previously reported myceloids formed by other Arthrobacter species after osmotic stress [ 30 ]. Hence the mutant fails to grow by snap division, but instead adopts non-separating myceloid growth, characteristic of the morphological switch of the wild-type when subjected to salt stress.…”
Section: Resultssupporting
confidence: 87%
“…Whereas the doubling time for the wild-type was 2.5 h, for the mutant it was 3.3 h, approximating the 3.2 h doubling time of the wild-type grown in salt-amended Luria broth (LB). When early log-phase cells were examined by phase-contrast microscopy, we observed extensive aggregate formation by the mutant, similar to previously reported myceloids formed by other Arthrobacter species after osmotic stress [ 30 ]. Hence the mutant fails to grow by snap division, but instead adopts non-separating myceloid growth, characteristic of the morphological switch of the wild-type when subjected to salt stress.…”
Section: Resultssupporting
confidence: 87%
“…In this regard? phages for A. oxydans and soil isolate SPI-1 were not detected in nutrient broth, soil extract, and cation-complete medium percolates, although these bacteria grew well on these media as pure cultures in the laboratory (13). Also, these bacteria were not detected when dilutions of natural nonpercolated soil were plated on nicotine agar, although they can use nicotine as their only source of carbon and nitrogen.…”
Section: Resultsmentioning
confidence: 95%
“…The potent rare actinobacterial strain isolated from Mango orchards of Vissannapet, which exhibited strong antagonistic activity, was identified as A. kerguelensis VL-RK_09. The detailed micromorphological studies through scanning electron microscopy revealed that the cells of the strain displayed rudimentary branching in the exponential phase and fragmented into coryneforms and coccoid elements at the stationary phase exhibiting the rod-coccus life style [16,17]. The SEM photograph of the strain is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%